A Review on Critical Success Factors for Total Productive Maintenance and Development of Research Framework - Bakri, Adnan; Ariff Mahzan, Muhd; Lutfi Zahin Ab Latif, Muhd (International Journal of Engineering and Technology, 2018)
Total Productive Maintenance (TPM) is holistic maintenance management approach aimed at integrating the role of maintenance and production department to share responsibility in taking care the production equipment of a company. In the right environment, TPM implementation would make significant contribution to companyâ€™s profitability particularly in increasing the production efficiency and improving the product quality. Despite many TPM implementation frameworks have been studied, there are still many companies, particularly under the classification of Small and Medium Enterprises (SMEs) are struggling and found themselves either failed right at the start-up or during the process of TPM implementation. Apparently, that there is still inadequate guidance about how TPM should be adopted, managed and integrated with other key quality initiatives in the SMEs environment. This paper is part of an ongoing research aimed at developing a framework for systematic TPM implementation in Malaysian SMEs. It focuses on the understanding of the concept of Critical Success Factors (CSFs) of TPM. The proposed conceptual framework will provide a holistic guidance and understanding of the CSFs to be adopted and adapted in managing the maintenance activities in Malaysian SMEs. This would enable the SMEs to improve their maintenance management practices in relation to world-class manufacturing standard.Â Â